Management Education – The philosophy of Education - Allegra, Stefania (International Journal of Scientific Research and Management (IJSRM), 2019)
It’s a duty for a person and for society. The education is related to the importance of culture, the place where you live it influences the education.You must take care about the level of the education that you can achieve. It’s important to get goals, forms, methods, and meaning of education. So philosophy education means philosophical analysis and pedagogical method applications.Universities move according to the importance of education. Today we find common themes about the philosophy of education that express the change in teaching, at all levels.Many philosophies influence the philosophy of education such as realism, idealism, positivism, empiricism, existentialism, Marxism.1